Maternal supplementation of different trace mineral sources on broiler breeder production and progeny growth and gut health - de Arruda Roque, Fabricia; Chen, Juxing; Araujo, Raquel B; Murcio, André Luis; de Souza Leite, Brunna Garcia; Dias Tanaka, Mylena Tückmantel; Granghelli, Carlos Alexandre; Pelissari, Paulo Henrique; Bueno Carvalho, Rachel Santos; Torres, David; Vázquez‐Añón, Mercedes; Hancock, Deana; et al. (Frontiers in Physiology, 2022)
The objective of this study was to determine maternal supplementation of trace mineral minerals on breeder production and progeny growth and development. 540 broiler breeders, Cobb 500 (0-66 weeks) were assigned to one of three treatment groups: ITM: inorganic trace minerals (Zn:Cu:Mn 100:16:100 ppm); MMHAC: mineral methionine hydroxy analog chelate (50% dose of ITM), and TMAAC: trace minerals amino acid complex (50% dose of ITM). Data were analyzed by one-way ANOVA; means were separated by Fisher’s protected LSD test. A P-Value ≤ 0.05 was considered statistically different. At 28wks of age, eggs from breeder treatments were hatched for progeny trial, 10 pens with 6 males and 6 female birds per pen were fed a common diet with ITM for 45d. Breeders on ITM treatment had higher body weight, weight gain and lower feed conversion ratio (FCR) from 0-10wks, when compared to birds fed MMHAC. MMHAC significantly improved egg mass by 3g throughout the reproductive period (26-66wks) in comparison to ITM. MMHAC improved egg yolk color versus (vs) ITM and TMAAC in all periods, except 28wks, increased eggshell thickness and resistance vs TMAAC at 58wks, and reduced jejunal NF-B gene expression vs TMAAC at 24wks. MMHAC and/or TMAAC reduced tibial dry matter weight, Seedor index and resistance in breeder at 18 wks. Maternal supplementation of MMHAC in breeder hens increased progeny body weight vs ITM and TMAAC at hatching, reduced feed intake vs ITM at d14 and d28, and improved FCR and performance index vs TMAAC at d28, reduced NF-B gene expression and increased A20 gene expression vs TMAAC on d0 and vs ITM on d14, reduced TLR2 gene expression vs ITM on d0 and vs TMAAC on d14, increased MUC2 gene expression vs both ITM and TMAAC on d45 in progeny jejunum. Overall, supplementation MMHAC improved breeder production and egg quality and reduced breeder jejunal inflammation while maintaining tibial development in comparison to those receiving ITM supplementation, and it also carried over the benefits to progeny with better growth performance, less jejunal inflammation and better innate immune response and gut barrier function in comparison to ITM and/or TMAAC.